Deployment Opportunities for Space Photovoltaics and the Prospects for Perovskite Solar Cells (Adv. Mater. Technol. 3/2022). Issue 3 (10th March 2022) - Ho‐Baillie, Anita W. Y.; Sullivan, Hamish G. J.; Bannerman, Thomas A.; Talathi, Harsh. P.; Bing, Jueming; Tang, Shi; Xu, Alan; Bhattacharyya, Dhriti; Cairns, Iver H.; McKenzie, David. R.
Abstract : Affordable Space Grade Energy Systems The rapid progress in space exploration, mining and tourism has been fuelled by both public and private sector investment. As we move into the era of 'commercial space', affordable space grade energy systems are important and new photovoltaic technologies will be required to reduce cost. In article 2101059, Anita W. Y. Ho‐Baillie and colleagues outline the major space markets and the opportunities for perovskite space solar cells.